Pengaruh Harga, Lokasi Dan Jenis Produk Terhadap Keputusan Pembelian Di Pasar Uka Terjun Medan Marelan - Agustina, Lisa; Sianturi, Charles M.; Simangunsong, Ridhon NB. (Research and Community Service UNIVERSITAS KALBIS, 2024)
The objective of this study to determine the effect of price, location and type of product on purchasing decisions, using quantitative research methods. The location of the study was at the UKA Terjun market, with 110 respondents who had shopped at the UKA Terjun market. Data collection was carried out by distributing questionnaires, using a Likert Scale. Data were processed using SPSS Version 25. Data analysis used multiple linear regression, and from the results of the data analysis, the multiple regression coefficient of variable X1 (Price) is 0.178, variable X2 (Location) is 0.251, variable X3 (Type of Product) is 0.707, and the R Square value is 0.444. It can be concluded that price, location and type of product have a positive and significant effect on purchasing decisions both through partial tests (t-test) and simultaneous tests (F-test). Price, Location, Product Type and Purchasing Decisions